Broadening the phenotypic spectrum and physiological insights related to EIF2S3 variants. Issue 7 (19th May 2021) - Moortgat, Stephanie; Manfroid, Isabelle; Pendeville, Hélène; Freeman, Stephen; Bourdouxhe, Jordane; Benoit, Valérie; Merhi, Ahmad; Philippe, Christophe; Faivre, Laurence; Maystadt, Isabelle
Abstract: Mental deficiency, epilepsy, hypogonadism, microcephaly, and obesity syndrome is a severe X‐linked syndrome caused by pathogenic variants in EIF2S3 . The gene encodes the γ subunit of the eukaryotic translation initiation factor‐2, eIF2, essential for protein translation. A recurrent frameshift variant is described in severely affected patients while missense variants usually cause a moderate phenotype. We identified a novel missense variant (c.433A>G, p.(Met145Val)) in EIF2S3 in a mildly affected patient. Studies on zebrafish confirm the pathogenicity of this novel variant and three previously published missense variants. CRISPR/Cas9 knockout of eif2s3 in zebrafish embryos recapitulate the human microcephaly and show increased neuronal cell death. Abnormal high glucose levels were identified in mutant embryos, caused by beta cell and pancreatic progenitor deficiency, not related to apoptosis. Additional studies in patient‐derived fibroblasts did not reveal apoptosis. Our results provide new insights into disease physiopathology, suggesting tissue‐dependent mechanisms. Graphical abstract: Stable CRISPR knockout zebrafish lines of eif2s3 exhibit microcephaly, apoptosis, and a decreased number of neuronal cells. They recapitulate the human microcephaly.